7) A solução da equação 5 (1 - x) - 2x + 1 = - 3 (2 + x) é:
a) -3
b)+3
c)0
d)-5


Resposta :

letra b) +3

5 (1 - x) - 2x + 1 = - 3 (2 + x)

5-5x-2x+1 = -6-3x

-5x-2x+3x = -6-5-1

-4x = -12

x = 12/4

x = +3

❤️ Boa noite ❤️

04/11/21

Ver imagem GLAUCIACKLESSPAA44T

Resposta:

Explicação passo a passo:

[tex]5.(1-x)-2x+1=-3.(2+x)[/tex]

[tex]5-5x-2x+1=-6-3x[/tex]

[tex]-5x-2x+3x=-6-5-1[/tex]

       [tex]-4x=-12[/tex]

          [tex]4x=12[/tex]

            [tex]x=12/4[/tex]

            [tex]x=3[/tex]

      [tex]Resposta:(b)[/tex]